2022
DOI: 10.1002/ctm2.1146
|View full text |Cite
|
Sign up to set email alerts
|

Loss of G0/G1 switch gene 2 (G0S2) promotes disease progression and drug resistance in chronic myeloid leukaemia (CML) by disrupting glycerophospholipid metabolism

Abstract: Tyrosine kinase inhibitors (TKIs) targeting BCR::ABL1 have turned chronic myeloid leukaemia (CML) from a fatal disease into a manageable condition for most patients. Despite improved survival, targeting drug‐resistant leukaemia stem cells (LSCs) remains a challenge for curative CML therapy. Aberrant lipid metabolism can have a large impact on membrane dynamics, cell survival and therapeutic responses in cancer. While ceramide and sphingolipid levels were previously correlated with TKI response in CML, the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 86 publications
(202 reference statements)
0
7
0
Order By: Relevance
“…SPP1 (encoding osteopontin) 31 , 32 , MAPK4 33 , SMO (encoding smoothened) 34 , 35 and FZD3 (encoding frizzled protein 3) 36 have known function as cancer progression promoters. Furthermore, there was down-regulation of tumor suppressor gene RBM47 37 , and the apoptotic regulator, G0S2 38 , 39 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SPP1 (encoding osteopontin) 31 , 32 , MAPK4 33 , SMO (encoding smoothened) 34 , 35 and FZD3 (encoding frizzled protein 3) 36 have known function as cancer progression promoters. Furthermore, there was down-regulation of tumor suppressor gene RBM47 37 , and the apoptotic regulator, G0S2 38 , 39 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, reduced expression of the G0S2 switch gene was observed in early stage resistant cells compared with control. The protein product of G0S2 canonically interacts with the apoptotic Bcl2 protein, which may have allowed a protective lowering of apoptosis 38 , 39 , 70 . G0S2 activity also results in a differentiation block and TKI resistance in CML cells 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Antidiabetic drugs, such as pioglitazone, bisbiguanide Alexidine (ALX), strongly cooperate with front-line therapies, promoting myeloid differentiation and decreasing the infiltration of LSC pool through stimulating transcription of CEBPβ and PPARγ. 59 As for the target therapy about lipid metabolism, it is suggested that FAO inhibitors (such as Avocatin B) can block energy support and induce an integrated stress response with high ROS formation, exerting synergistic effect with current chemotherapeutic drugs in AML. 56 BMAds also secret elevated asparagine and glutamine in ALL, inhibiting the L-asparaginase (ASNase)-induced toxicity.…”
Section: Bmads In Hematological Malignanciesmentioning
confidence: 99%
“…In recent years, the importance of lipid homeostasis in LSC‐target therapy attracts increasing attention. Antidiabetic drugs, such as pioglitazone, bis‐biguanide Alexidine (ALX), strongly cooperate with front‐line therapies, promoting myeloid differentiation and decreasing the infiltration of LSC pool through stimulating transcription of CEBPβ and PPARγ 59 …”
Section: Bmads In Hematological Malignanciesmentioning
confidence: 99%
“…This particular role of FAO in the survival of leukemic cells was also underlined in a demonstration of the overexpression of the enzyme 3-very long chain acyl-CoA dehydrogenase (VLCAD) in AML, of which a decrease in proliferation can be induced by gene attenuation or pharmacological inhibition via alteration of the Krebs cycle [ 4 ]. Additionally, a recent study demonstrated that glycerophospholipid metabolism is involved in drug resistance in chronic myeloid leukemia through downregulation of the G0/G1 switch gene 2 (G0S2), which confers worse overall survival to patients [ 5 ]. Similarly, Carnitine Palmitoyltransferase 1A (CPT1A), a key enzyme in carnitine-dependent transport across the mitochondrial inner membrane of FAs, was found to be overexpressed in bone marrow samples from AML patients with poor prognosis compared to those with normal bone marrow [ 6 ].…”
Section: Introductionmentioning
confidence: 99%